Modern recording techniques - Huber, David Miles; Runstein, Robert E. (Audio Engineering Society presents., 2018)
Master the tools and day-to-day practices of music recording and production. Learn the ins and outs of room acoustics and designing a studio. Gain techniques for mic placement and running a session. Get a solid grounding in both theory and industry practice.